Daily Practice Experience of Baricitinib Treatment for Patients with Difficult-to-Treat Atopic Dermatitis: Results from the BioDay Registry - Celeste M. Boesjes; Esmé Kamphuis; Nicolaas P.A. Zuithoff; Daphne S. Bakker; Laura Loman; Lotte S. Spekhorst; Inge Haeck; Marijke Kamsteeg; Anneke M.T. van Lynden-van Nes; Floor M. Garritsen; Klaziena Politiek; Marja Oldhoff; et al. (Medical Journals Sweden, 2022)
Clinical trials have shown that baricitinib, an oral selective Janus kinase 1/2 inhibitor, is effective for the treatment of moderate-to-severe atopic dermatitis. However, daily practice data are limited. Therefore, this multicentre prospective study evaluated the effectiveness and safety of 16-weeks' treatment with baricitinib in adult patients with moderate-to-severe atopic dermatitis in daily practice. A total of 51 patients from the BioDay registry treated with baricitinib were included and evaluated at baseline and after 4, 8 and 16 weeks of treatment. Effectiveness was assessed using clinician- and patient-reported outcome measurements. Adverse events and laboratory assessments were evaluated at every visit. At week 16, the probability (95% confidence interval) of achieving Eczema Area and Severity Index ≤ 7 and numerical rating scale pruritus ≤ 4 was 29.4% (13.1-53.5) and 20.5% (8.8-40.9), respectively. No significant difference in effectiveness was found between dupilumab non-responders and responders. Twenty-two (43.2%) patients discontinued baricitinib treatment due to ineffectiveness, adverse events or both (31.4%, 9.8% and 2.0%, respectively). Most frequently reported adverse events were nausea (n = 6, 11.8%), urinary tract infection (n = 5, 9.8%) and herpes simplex infection (n = 4, 7.8%). In conclusion, baricitinib can be an effective treatment option for moderate-to-severe atopic dermatitis, including patients with non-responsiveness on dupilumab. However, effectiveness of baricitinib is heterogeneous, which is reflected by the high discontinuation rate in this difficult-to-treat cohort.